(untitled) (ACME, 2020)
Few authors have been able to represent poverty with the intelligence and compassion shown by Dickens. And yet little scholarship has been devoted to the relationship between the Victorian novelist and the paupers of his times. This paper investigates the evolution of the idea of poverty in some of Dickens’s works, from his early novel Oliver Twist to his more mature Bleak House. At a time when the understanding of poverty was dominated by the agenda of the Poor Law Commission, Dickens seems to move from a spontaneous and religious empathy with the poor, to a more sophisticated view of poverty, which he tackles in all its social and human complexity. Indeed Dickens’s poetics allows him to offer a glimpse into the complexity of the poor’s predicament, gainsaying the Victorian notion that indigent people could be sorted into two or three categories and managed accordingly.